Accuracy of the new rapid test for monitoring adalimumab levels. (February 2019) - Rocha, Cátia; Afonso, Joana; Lago, Paula; Arroja, Bruno; Vieira, Ana I.; Dias, Claudia C.; Magro, Fernando
Background: The loss of response to adalimumab (ADL) has been related to low serum concentrations at trough. Currently, most methods commercially available for the quantification of ADL are enzyme-linked immunosorbent assay (ELISA) based, with a turnaround time of approximately 8 h, delaying the target dosage adjustment to the subsequent infusion. In this study, we aimed to evaluate the performance of the newly available rapid-test ADL quantification assay by comparing it with three established ELISA methods, using spiked samples and a set of clinical samples. Methods: Spiked samples from control donors and 120 serum samples from inflammatory bowel disease (IBD) patients undergoing ADL therapy were quantified using lateral flow Quantum Blue ® Adalimumab and, the ELISA formats from Immundiagnostik, R-Biopharm and an in-house assay. Results: The rapid-test assay had intraclass correlation coefficients of 0.590, 0.864 and 0.761 when comparing with the Immundiagnostik, R-Biopharm and in-house assays, respectively. For the five therapeutic windows, the accuracy was high: ADL rapid test compared with the Immundiagnostik (58–88%); R-Biopharm, 68–89%; and in house, 60–88%; and kappa statistics revealed 0.492–0.602, 0.531–0.659 and 0.545–0.682, respectively. Conclusions: The Quantum Blue ® Adalimumab assay can replace the commonly used ELISA-based ADL quantification kits and it is a reliable alternative to these methods. This rapid-test assay enables the quantitative determination of ADL serum trough level in only 15 min. The developed assay allows measurement of ADL over a wide range. Hence, it represents a valuable tool for the clinician to assess the ADL trough level.